2014
DOI: 10.1097/aln.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

OPRM1A118G Gene Variant and Postoperative Opioid Requirement

Abstract: The OPRM1 A118G polymorphism was associated with interindividual variability in postoperative response to opioids. In a subpopulation, identifying OPRM1 A118G polymorphism may provide valuable information regarding the individual analgesic doses that are required to achieve satisfactory pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 70 publications
(88 reference statements)
2
84
0
Order By: Relevance
“…Meta-analyses suggest that carrying the OPRM1-118G allele increases postsurgical opioid analgesic requirement (Hwang et al, 2014), although association with opioid dependence is not robust outside of Asian populations (Haerian and Haerian, 2013). It is possible that, given our findings, decreased drug reward is protective against opioid abuse in some individuals, while resistance to negative drug effects promotes intake in others.…”
Section: Discussionmentioning
confidence: 93%
“…Meta-analyses suggest that carrying the OPRM1-118G allele increases postsurgical opioid analgesic requirement (Hwang et al, 2014), although association with opioid dependence is not robust outside of Asian populations (Haerian and Haerian, 2013). It is possible that, given our findings, decreased drug reward is protective against opioid abuse in some individuals, while resistance to negative drug effects promotes intake in others.…”
Section: Discussionmentioning
confidence: 93%
“…Genetic factors can also impact postoperative analgesic responses, which may impact CPSP since acute pain severity is among the strongest predictors of CPSP. In addition to multiple genes that impact drug metabolism [144], COMT [29,36] and OPRM1 [80,152] have been associated with postoperative opioid analgesic requirements.…”
Section: General Considerationsmentioning
confidence: 99%
“…On the other hand, higher binding affinity for endogenous opioids has been found, as discussed in (49 ). More recently, 2 independent metaanalyses on postoperative pain in adults, sample size 4607 (49 ) and 3144 (18 ) respectively, showed that carriers of the 118AϾG variant have indeed higher opioid requirements (17,50 ) and a lower risk for adverse events (17 ).…”
Section: Oprm1mentioning
confidence: 99%